PENINGKATAN KEPUASAN PASIEN MELALUI KUALITAS PELAYANAN DAN FASILITAS PELAYANAN (Studi Pada Poli Gigi Umum RSGM Gusti Hasan Aman di Banjarmasin) - Selviana Rizky Pramitha; Fitriana Cessar Putri; Rahmi Widyanti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
Aims this research to analyzes influence patient satisfaction are service quality and facilities. The data collected by questionnaires and direct surveys to obtain the necessary data regarding the influence of service quality and service facilities on patient satisfaction at the General Dental Clinic of RSGM Gusti Hasan Aman in Banjarmasin. Result this research: 1) Service quality partially influences patient satisfaction at RSGM Gusti Hasan Aman General Dental Policlinic with a sig = 0.000 and t-count 7.139 > t-table, 2) Service facilities partially influence patient satisfaction at RSGM General Dental Policlinic Gusti Hasan Aman with a sig value = 0.000 and t-count 3.876> t-table, 3) Quality of service and service facilities simultaneously influence patient satisfaction at the Gusti Hasan Aman General Dental policlinic with a calculated F value (53.334)> 3.104 (F table) and sig (0.000) < 0.05, 4) Service quality has a dominant influence on patient satisfaction at the General Dental policlinic of RSGM Gusti Hasan Aman with a regression coefficient value of 0.665. This can be interpreted as saying that the quality and service facilities provided by RSGM Gusti Hasan Aman are adequate so that together they can fulfill the patient's wishes. If the patient's wishes are fulfilled it will increase patient satisfaction.